Influence of NO2, NO and meteorological conditions on the tropospheric O3 concentration at an industrial station. (December 2020) - Paraschiv, Spiru; Barbuta-Misu, Nicoleta; Paraschiv, Simona Lizica
Abstract: Combustion of fossil fuels (even biomass combustion) to produce energy and heat for the industry is the most important anthropogenic source of nitrogen oxides (NOx=NO+NO2 ). Although NO2 is not a greenhouse gas, it is the precursor to the formation of such a gas, namely tropospheric ozone. Energy-intensive industries contribute up to 45% to the global greenhouse gas emissions, so to keep global warming below 1.5 °C according to the Paris Agreement requirements, CO2 emissions must be close to zero by 2050, so the industrial sector must be decarbonized. All decisions on reducing pollutant emissions and not just those of CO2 (by capturing and storing them), will lead to lower fossil fuel consumption and will increase energy efficiency in the industry and reduce greenhouse gas (GHG) emissions. The paper analyzes the synergistic effects of pollutants (NO2, NO), emitted by industry energy use, and meteorological factors in the formation of tropospheric ozone at an industrial site using Pearson's correlation. Pearson's correlation showed that the ozone concentration was significantly correlated with NO2, NO pollutants and the meteorological factors. Among them, NO2, NO, and relative humidity were negatively correlated with the O 3 concentration. We observed a significant positive correlation between solar radiations, air temperature and wind speed with O 3 concentration during the study period. Graphical abstract: